Circulating endothelial progenitor cells are increased in human lung cancer and correlate with stage of disease - Nowak, Kai; Rafat, Neysan; Belle, Sebastian; Weiß, Christel; Dacho, Christine; Hohenberger, Peter; Beck, Grietje (European journal of cardio-thoracic surgery, 2010)
Aim: Recent studies suggest that circulating endothelial progenitor cells (cEPCs) are recruited to the angiogenic vascular system of non-small-cell lung cancer (NSCLC) and correlate with clinical behaviour. Consequently, the level of cEPCs has been proposed as a novel biomarker for disease progression in NSCLC. The role of cEPCs for the vascularisation of small-cell lung cancer (SCLC) is still unknown. Therefore, this study aims to examine the level of cEPCs as well as the level of EPC mobilising mediators in the blood of lung cancer patients and the correlation with tumour stage and disease progression. Methods: In this study, 36 patients with biopsy-proven lung cancer (32 NSCLC, 4 SCLC) and 15 healthy individuals were recruited. Peripheral blood mononuclear cells (PBMCs) were isolated by Ficoll density gradient centrifugation, and cEPCs were characterised by triple staining using antibodies against CD133, CD34 and vascular endothelial growth factor-receptor (VEGFR)-2. Serum concentrations of VEGF were determined by enzyme-linked immunosorbent assay (ELISA). Results: In lung cancer patients, the number of cEPCs was significantly higher than in healthy controls (p = 0.000). Regarding tumour stage, NSCLC patients with UICC III-IV had significantly higher EPC counts than UICC I-IIB patients (p = 0.044). Serum VEGF concentrations in lung cancer patients were significantly higher than in healthy controls (p = 0.000) and correlated with cEPC numbers for all the groups (r = 0.42, p = 0.003). Follow-up data (n = 20) revealed significantly higher cEPC numbers in lung cancer patients with tumour progression than in patients without evidence or progression of disease. The relative change in cEPC numbers between pre- and post-treatment assessment was significantly correlated to disease progression (p = 0.000, log rank test) and the combined end points of progression and/or death (p = 0.003, log rank test). Conclusion: Our results show increased cEPCs numbers in lung cancer patients, which may play a role in the vascularisation of lung cancer. Moreover, our results suggest an association of cEPC numbers with tumour stage and progression.